Hverdagsrehabilitering - integrert eller spesialisert? - Birkeland, Arvid Karl; Langeland, Eva; Tuntland, Hanne; Jacobsen, Frode F.; Førland, Oddvar (Nordisk tidsskrift for helseforskning, 2018)
This study was part of a major evaluation project with focus on various models for and effects of reablement. The aim was to get an extended understanding of how Norwegian municipalities organize and conduct reablement. Seven focus group interviews were conducted in seven municipalities including a total of 33 participants representing different health professions. The interviews were transcribed, and a hermeneutical approach was used in the analyses. Four main themes were derived: "The team as an organizational and professional center", "Collaboration around assessment of applications”, "Different understanding of rehabilitation affected the organization", and "Goal – oriented and intensive training in everyday activities". The focus group interviews revealed different strength and weaknesses with specialized or integrated organization of reablement, but nevertheless they emphasized the importance of having interdisciplinary teams that can coordinate and participate in the practical implementation. However, more research is necessary to get more knowledge about organization of reablement. Keywords/Nøkkelord reablement; organizing; team; specialized; integrated; home care services hverdagsrehabilitering; organisering; team; spesialisert; integrert; hjemmetjenesten